Review of mainstream-heterodox approaches relations in Economics for the digital transition - Sánchez-Bayón, Antonio (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
This is a critical and comparative review on Economics, with special attention to the mainstream-heterodox approaches relations, during the implementation of formalist positivism promoted by the Neoclassical Synthesis, under the instrumental reduction and mathiness, so it means less realism and adaptation ability for main changes happened. Beyond the rise and fall of the mainstream economic modelization (or McDonalization), there is an urgent reformulation after the Great Recession, given its incapacity to predict any crisis or to attend the digital economy. This review follows the theoretical and methodological frameworks of the mainline heterodox approaches, because they are compatible and in favor to dialogue with other schools, as well as allowing for teaching of a more realistic and meaningful Economics for students.